THE BIBLIOMETRIC ANALYSIS OF SERVICE RECOVERY RESEARCH BASED ON SCOPUS DATA: NETWORK MAPPING AND TOPIC TRENDS USING VOSVIEWER - Riyan Falah Al Wahid; Retno Widowati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research employed a bibliometric analysis of 170 Scopus-indexed articles from 2020 to 2025 period to map the intellectual landscape and current trends in service recovery research. The analysis revealed that publication trends peaked in 2022, followed by consolidation and deepening of themes in subsequent years. Business, management, and accounting fields dominate (50%), with the United States and China being the main contributors. Keyword network mapping identifies a significant shift in research focus from traditional concepts toward digital technology integration, with artificial intelligence, chatbot, and social media emerging as the most relevant and interconnected topics. This research key findings highlighted the identification of brand-related dimensions (brand trust, brand equity) as increasingly crucial but still fragmented thematic clusters in the literature. Additionally, potential areas for future research were mapped, particularly in underexplored domains such as Generative AI and specific industry contexts. This study, hopefully, complements previous bibliometric research limitations by presenting a more up-to-date temporal scope and a sharper analytical focus on digital and brand contexts